In vitro studies of Brazilian propolis against a phytopathogen agent: analyzing bioactivity and mechanism of action in model membranes - Pazin, Wallance Moreira; Santos, Suikinai Nobre; Queiroz, Sonia Claudia; Soares, Ademilson Espencer Egea; Ito, Amando Siuiti (Revista Brasileira de Física Médica, 2016)
Studies of amphiphilic aggregates, like phospholipid vesicles, are extremely important to understand cell membranes, structures that involve cells and constituted mainly of lipids and proteins, held together by non-covalent interaction. Different drugs act in target cells modifying structural properties of membranes, during the action against many types of diseases. Brazilian propolis are attractive phytotherapeutic products due to their wide spectrum of preventive actions and treatment of diseases, showing antimicrobial, antitumoral and antioxidant activities. In this study, we performed bioassays to investigate the action of four types of Brazilian propolis against the pseudofungus Pythium aphanidermatum, a phytopatogen which attacks and rots roots and fruits of different types of vegetation. The interaction of the most bioactive propolis with model membranes made of zwitterionic and anionic unilamellar vesicles was studied by means of fluorescence measurements (time-resolved fluorescence and fluorescence lifetime image miscroscopy). We observed that compounds present in the most bioactive propolis present high interaction with nano-organized amphiphilic structures greatly modifuing their physicochemical and structural properties.